Activities of β-Lactams and Macrolides against Helicobacter pylori - Hassan, Ibrahim J. (American Society for Microbiology, 1999)
A continuous-culture system (chemostat) was used to study the activities of β-lactam antimicrobial agents, clarithromycin, and 14-OH-clarithromycin against slowly growing Helicobacter pylori NCTC 11637. H. pylori was grown to steady state before exposure to these antimicrobial agents at ×8 the MIC. The bactericidal actions of combinations of amoxicillin and clarithromycin were also studied. Viable counts (numbers of CFU per milliliter) were determined at 2-h intervals for 12 h and at 20 h after the addition of antibiotics. The effects of pH changes (6.5 to 7.4) on the activities of amoxicillin, clarithromycin, and the combination of these against H. pylori NCTC 11637 were also studied. Viable counts following exposure to ampicillin, cefixime, ceftazidime, cefuroxime, cefotaxime, azlocillin, and piperacillin at 20 h showed bacteriostatic activity. Imipenem, meropenem, amoxicillin, clarithromycin, and 14-OH-clarithromycin reduced the viable counts by 3 log(10) CFU/ml (≥99.9% killing). Imipenem was the most rapidly bactericidal against H. pylori NCTC 11637. Results of the pH experiments showed that amoxicillin was bactericidal at pHs 6.5 to 7.4. Clarithromycin was bactericidal at pH 7.0 to 7.4 but was bacteriostatic at pH 6.5. The combination of amoxicillin and clarithromycin was bactericidal at pHs 6.5 and 7.0. A batch culture (flask system) was also used to investigate 12 strains of H. pylori for their susceptibilities to β-lactams, clarithromycin, and/or 14-OH-clarithromycin in order to determine whether results from the chemostat model can be reproduced with batch cultures. Results of the chemostat time-kill kinetic study were reproducible in our batch culture flask system. The role of carbapenems in the eradication of H. pylori should be investigated.